PENYEMPURNAAN SISTEM PENGELOLAAN AIR IRIGASI MENGHADAPI IRIGASI MODERN DI INDONESIA - Soekrasno Soekrasno (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2018)
Damage to irrigation areas in Indonesia covering an area of 0.37 million hectares for severe damage and an area of 1.25 million hectares for moderate and mild damage, has an impact on Indonesia's ability in rice production; rice imports were almost half a century, and only the adequacy of rice was 2 X, i.e. 1984 and 2009. This was due to low irrigation services which resulted in less optimal carrying capacity of food security. The deterioration in the function of irrigation services can be grouped into 5 causes of low irrigation pillars, namely: vulnerability of water sources, lack of irrigation infrastructure, low irrigationwater management, weak management institutions, and low human resources. The cause will be eliminated by the irrigation modernization program by working on these five pillars. One of the pillars in the modernization of irrigation that needs to be improved is the irrigation management system. The purpose ofthis paper is to contribute ideas in improving the irrigation management system in Indonesia. The author has conducted observations and research on several irrigation areas, both the authority of the Central, Provincial and District Governments, especially visits to DI Wadaslintang, Central Java and DI Bondoyudo, East Java concerning irrigation water management systems. What stands out is the low level of irrigation services due to the inefficient irrigation water management system in Indonesia, in addition to the nature of service-based provision and not service-oriented based on farmers' needs. Identification wascarried out on the DI to find out the reasons for the low irrigation water management system, namely: orientation to water supply, calculation of irrigation requirements, water allocation method, irrigationwater distribution schedule, irrigation water loss, irrigation operational steps, irrigation water productivity measurement This study analyzes the factors causing the low irrigation water management system while making a formula for the improvement proposal in the form of 7 steps.